TUBULAR STRENGTH COMPARISON OF OFFSHORE JACKET STRUCTURES UNDER API RP2A AND ISO 19902 - Idrus, Arazi (the Institution of Engineers Malaysia, 2011)
Offshore jacket platforms in Malaysia are designed using API RP2A Working Stress Design (WSD) code. WSD code has proved its effectiveness and has been in use for long time, but it needs to be changed into Load and Resistance Factor Design (LRFD) based code which is being followed by all building code agencies. In WSD, design safety factor is provided only on resistance side and is based on judgement and experience. In place of WSD, Limit State Design or LRFD has proved to be more rational as it is based on probabilistic models. The reliability of jacket platforms is maintained in API RP2A LRFD by setting target safety factor the same as that provided in WSD designs, which means structures designed as per LRFD code will have the same reliability as API RP2A WSD (which has already provided safe structures and the best available practice for design). When adopting LRFD methodology, the appropriate load and resistance factors can be optimised through the process of calibration. Knowledge of the strength equations in the different codes and the similarities and differences between them is useful for the calibration. The first step in the calibration process is the determination of reliability of structural tubular members of the jacket designed as per existing practice of WSD and LRFD code. Here in this research, API RP2A WSD code and International Standard Organization (ISO 19902) (LRFD based code) are taken into consideration for the reliability analysis. In this paper, the relevant strength equations of three codes are identified and compared and the similarities and differences are determined for tubular members which are the main part of jacket structures.